2016
DOI: 10.1007/s11899-016-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with MYC-Altered Lymphomas

Abstract: Patients diagnosed with non-Burkitt high-grade B cell non-Hodgkin lymphomas demonstrating rearrangement in MYC, an oncogene promoting cellular proliferation, frequently do not achieve long-term disease-free survival due to a suboptimal response to standard front-line and salvage therapies. Double-hit lymphomas, harboring rearrangements in MYC as well as BCL2 and/or BCL6, appear to carry a particularly poor prognosis, although patients with this disease appear to achieve better survival outcomes when treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…4 Initially, researchers found BCL6 mainly abundantly expressed in B cell and CD4 + T cell in germinal centers of normal lymphoid tissues, 22 and the association of BCL6 with lymphoma has been widely investigated and well established, 3,5,22 especially in diffuse large B-cell lymphoma, 23 the pathogenesis mechanisms attribute to rearrangements or somatic mutations of BCL6, and so on. 4,24,25 BCL6 inhibits p53 expression in germinal center of B lymphocyte 26 and interacts with pro-oncogene c-myc to accelerate the carcinogenesis of lymphoma. 27 Based on these findings, BCL6 inhibitors (compound 79-6 28 or retroinverso BCL6 peptide inhibitor (RI-BPI) 29 ) have been developed and showed delightful potential application prospect as a therapeutic strategy for patients with hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…4 Initially, researchers found BCL6 mainly abundantly expressed in B cell and CD4 + T cell in germinal centers of normal lymphoid tissues, 22 and the association of BCL6 with lymphoma has been widely investigated and well established, 3,5,22 especially in diffuse large B-cell lymphoma, 23 the pathogenesis mechanisms attribute to rearrangements or somatic mutations of BCL6, and so on. 4,24,25 BCL6 inhibits p53 expression in germinal center of B lymphocyte 26 and interacts with pro-oncogene c-myc to accelerate the carcinogenesis of lymphoma. 27 Based on these findings, BCL6 inhibitors (compound 79-6 28 or retroinverso BCL6 peptide inhibitor (RI-BPI) 29 ) have been developed and showed delightful potential application prospect as a therapeutic strategy for patients with hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The MYC gene is widely studied in lymphoma, prostate cancer, colorectal cancer and small cell lung cancer, 39 42 and several studies have shown that overexpression of MYC is associated with drug resistance. 43 , 44 Brägelmann et al 17 pointed out that as a carcinogenic driving factor, MYC may constitute a new therapeutic target in small cell lung cancer, and its core role in tumor maintenance provides a new opportunity for targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The asterisk denotes statistical significance in a pairwise comparison (p < .05) [Color figure can be viewed at wileyonlinelibrary.com] that is, IG-MYC occur in BL, single-hit, and double-hit lymphomas (Aukema et al, 2014). Single-hit and double-hit lymphomas with IG-MYC or another translocation partner of MYC (non-IG-MYC) have a poorer prognosis than standard DLBCL, which may be improved with intensive chemotherapy (de Jonge et al, 2016;Landsburg, 2016;Landsburg et al, 2016). Recognition of MYC-rearranged lymphomas is, therefore, crucial to proper management and improvement of clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%